International Kidney Paired Donation – The Experience of a Single Center - José Francisco; Renata Carvalho; Joana Freitas; Miguel Trigo Coimbra; Sara Vilela; Manuela Almeida; Sandra Tafulo; Rosário Caetano Pereira; Catarina Bolotinha; Margarida Ivo; Susana Sampaio; Catarina Ribeiro; et al. (Brazilian Journal of Transplantation, 2023)
Introduction: Kidney transplantation is the preferred treatment for end-stage renal disease, but organ scarcity can result in longwaiting times. Living-donor kidney transplantation offers an alternative to deceased donation, but HLA or AB0 incompatibility can pose a significant obstacle. This study aimed to show the results achieved by a portuguese hospital since its integration into an international cross-over program, the South Alliance for Transplants (SAT). Methods: The SAT program was founded in 2017 and is composed of ten Spanish hospitals, three Italian hospitals and one Portuguese hospital. The program runs every 4 monthsand enrolled only pairs that were incompatible. Organ transportation is carried out in partnership with the Portuguese Air Force. Results: Three distinct cross-over kidney transplants were performed in partnership with three Spanish hospitals, culminating in the transplantation of three Portuguese patients out of a total of seven patients. The first swap was performed in March 2020, at the beginning of the COVID-19 pandemic, in partnership with two Portuguese and one Spanish hospital. It involved one donor/recipient pair from each country, with AB0 incompatibility between the Portuguese donor and recipient, and no complications were reported. The second swap occurred in December 2021, with three donor/recipient pairs (one Portuguese, where the recipient presented anti- donor antibodies and positive crossmatch with the potential donor, and two from two Spanish hospitals). It was complicated by type-IB cellular rejection in the Portuguese recipient, one week after transplantation, which was treated with corticosteroid therapy. The third swap, also in December 2021, involved two donor/recipient pairs (one Portuguese and one Spanish). It was complicated by delayed renal function due to acute tubular necrosis (histological diagnosis) in the Portuguese recipient. At follow-up, the patients‘serum creatinine levels were within normal limits, and no other unexpected outcomes were recorded. Conclusion: SAT program has allowed some successful cross-over kidney transplants, probably improving the outcomes of kidney transplantation in Portugal. The expansion of such programs may contribute to a more efficient use of the available resources, increasing the number of transplants performed and reducing waiting times.